(untitled) (Journal for Freedom of Conscience (Jurnalul Libertății de Conștiință), 2022)
Essential Components of Freedom of Conscience and Religious Freedom in the Russian Federation in the Light of the European Convention on Human Rights The right to freedom of conscience and religious freedom are intended to defend and guarantee perhaps the most private and deepest values of a person. This article describes the components of these rights from the perspective of the European Convention on Human Rights, in the context of the „Yarovaya law” or „Yarovaya package” and its effects on missionary activity in Russian society. In society and public space, religious freedom includes the act of preaching, proselytizing and spreading the faith, otherwise the freedom of conscience and religion would be meaningless.